Experimental and computational study of latex clearing protein LcpK30 for rubber degradation - Abu Hassan, Aziana (2024)
The demand for rubber products grows exponentially. This condition results in significant amounts of rubber waste in the environment. Most of the rubber waste would come from synthetic rubber. Rubber waste management without a sustainable strategy will harm the environment and the general public's health. This work aims to introduce a sustainable approach to degrading rubber using enzymes. Latex-clearing protein K30 (LcpK30) catalyses the oxidative cleavage of the C=C bond in cis-1,4-polyisoprene natural rubber (NR). This enzyme can degrade synthetic polyisoprene, but the degradation rate is still low, and its potential to degrade other diene rubbers remains poorly understood. The ability of LcpK30 to interact with a sizeable hydrophobic substrate is interesting. It thus raises the question of how the substrates can access the catalytic site that is buried inside the protein cavity.